Keanekaragaman Jenis Tumbuhan Penutup Tanah Berpasir di Sekitar Muara Sungai Hitam Kota Bengkulu - Farma, Albert; Wiryono; Susatya, Agus; Septiyani, Faridatin (Jurnal Ilmu Ilmu Kehutanan, 2025)
The estuarine of Sungai Hitam in Bengkulu City represents a sandy terrestrial ecosystem characterized by a diverse assemblage of ground cover species, which collectively contribute to the ecological functionality of the immediate environment. This study aimed to identify the structural characteristics, species composition, and species diversity of the ecosystem's constituent flora. Fieldwork was conducted from January to February 2018. Data collection involved the systematic placement of 1m x 1m quadrat plots at 20m intervals. Subsequent data analysis utilized the Important Value Index (IVI) and Shannon-Wiener Diversity Index (H') equations. The findings revealed the presence of 79 species distributed across 22 families of ground cover plants. Sphagneticola trilobata (L.) was identified as the dominant species within this area, attributed to its robust adaptive capabilities and invasive characteristics. Despite this dominance, the overall species diversity was classified as high, evidenced by a diversity index value of 3.21. This high index signifies a relatively stable community structure and considerable ecological resilience against environmental disturbances.